(untitled) (International Journal of Engineering and Computer Science, 2017)
Another safe picture transmission method is proposed, which changes actually a given gigantic volume mystery picture into a mystery section unmistakable picture called mosaic picture of a similar size. The mosaic picture, which seems, by all accounts, to resemble a discretionarily picked target picture and might be used as a camouflage of the mystery picture, is yielded by isolating the mystery picture into areas and changing their shading ascribes to be those of the looking at bits of the objective picture. Dexterous procedures are planned to lead the shading change handle so mystery picture might be recovered losslessly. A plan of taking care of floods/undercurrents in the changed over pixels shading values by recording the shading contrast in the untransformed shading space is also proposed. The information required for recovering the mystery picture is installed into the made mosaic picture by a lossless data hiding arrangement utilizing a key. Great test comes about exhibit the achievability of the proposed technique. Index terms: Color Transformation, data hiding, image encryption, secure image transmission, mosaic image